Individual Freedom in the Legal Discourse in Indonesia - Agustinus, Eko (Indonesia Media Law Review, 2022)
Indonesia is one of the countries included in the state law. Law is a rule that can not be separated from our daily life where every joint of our lives is in the shade of law. Laws other than to protect us from abuse of power, the law is also used to uphold justice. This freedom is the hallmark of modern society today. But freedom has certain qualities. A free individual does not mean that they can do things themselves, such as damaging their surroundings, destroying other people's goods, harassing a man's wife or husband and so on. Of the 1945 Constitution Article 28 E is Everyone is free to embrace religion and worship according to his religion, choosing education and teaching, choosing a job, choosing citizenship, choosing a residence in the territory of the country and abandoning it, and the right to return, Everyone has the right to freedom of belief, expression of thoughts and attitudes, in accordance with his conscience, Everyone has the right to freedom of association, assembly, and expression.